PEMAHAMAN GEREJA MASEHI ADVENT HARI KETUJUH JEMAAT MERBABU TENTANG CARA HIDUP JEMAAT MULA-MULA BERDASARKAN KISAH PARA RASUL 2:44,45 - Jennedy Isaiah Dolot; Bartholomeus Diaz Nainggolan (Fakultas Filsafat Universitas Advent Indonesia, 2016)
The author gives title to this study, “The Understanding of the Merbabu Seventh-dayAdventist Church Bandung about the Way of Living of the Early Church Based onActs 2: 44.45.” The author is motivated by the way of life of the church today that isalready away from the way of life of the church should, like the way of life of theearly church. At the present time many churches who do not care to about the poor,the church members had no care for other people who are around them, it can beseen in the church, that there was the rich and the poor. The author chose MerbabuBandung church to be a place of the research of the author. The author will discussthree issues in this writing. First, how the understanding of the Merbabu churchabout this verses, the second is, how the experts of the bible comments related to thispassage, and the third, according to this verse, how should be the church life, or doesthis verses only for the early church, or to the church in these days also.Answering the field conclusion, the authors have conducted research in thecongregation Merbabu, it turns out the church generally has been understood aboutthe meaning of the verse in Acts 2: 44.45. The Church should have a special cash tohelp poor people who are in the church. But not only the church, but each memberas individual base must be attentive to the needs of their fellow man in need. Inconclusion theory, the Bible experts gave their comments with respect thereto. EarlyChurch can perform these characteristics due to several important factors. The giftof their love of Christ among them, the Holy Spirit is with them after the event ofPentecost. These things allow members of the early church to care for one another.Therefore, it ought to God's people today live life together. The congregation iscurrently devoted by God to care for the poor that is between them, in the practice ofstewardship, the church is also a place where all people get the attention of others. Inaddition, church members, as well as individuals, should pay attention to each other,just like what was done by the members of the early church